Four cases of cytokine storm after COVID-19 vaccination: Case report - Murata, Kazuhiro; Nakao, Naoki; Ishiuchi, Naoki; Fukui, Takafumi; Katsuya, Narutaka; Fukumoto, Wataru; Oka, Hiroko; Yoshikawa, Naotaka; Nagao, Takafumi; Namera, Akira; Kakimoto, Naoya; Oue, Naohide; et al. (Frontiers in Immunology, 2022)
The global coronavirus disease 2019 (COVID-19) pandemic has led to the rapid development of vaccines against this disease. Despite the success of the international vaccination program, adverse events following vaccination, and the mechanisms behind them, remain poorly understood. Here we present four cases of death following receipt of a second dose of COVID-19 vaccine, with no obvious cause identified at autopsy. Using RNA sequencing, we identified genes that were differentially expressed between our post-vaccination cases and a control group that died of blood loss and strangulation. Three hundred and ninety genes were found to be upregulated and 115 genes were downregulated in post-vaccination cases compared with controls. Importantly, genes involved in neutrophil degranulation and cytokine signaling were upregulated. Our results suggest that immune dysregulation occurred following vaccination. Careful observation and care may be necessary if an abnormally high fever exceeding 40°C occurs after vaccination, even with antipyretic drugs.